The Therapeutic Odyssey: Positioning Genomic Sequencing in the Search for a Child's Best Possible Life. Issue 3 (3rd July 2021) - Childerhose, Janet Elizabeth; Rich, Carla; East, Kelly M.; Kelley, Whitley V.; Simmons, Shirley; Finnila, Candice R.; Bowling, Kevin; Amaral, Michelle; Hiatt, Susan M.; Thompson, Michelle; Gray, David E.; Lawlor, James M. J.; et al.
Abstract: Background: The desire of parents to obtain a genetic diagnosis for their child with intellectual disability and associated symptoms has long been framed as a diagnostic odyssey, an arduous and sometimes perilous journey focused on the goal of identifying a cause for the child's condition. Methods: Semi-structured interviews (N = 60) were conducted with parents of children (N = 59, aged 2–24 years) with intellectual disability and/or developmental delay (IDD) who underwent genome sequencing at a single pediatric multispecialty clinic. Interviews were conducted after parents received their child's sequencing result (positive findings, negative findings, or variants of unknown significance). Thematic analysis was performed on all interviews. Results: Parents reported that obtaining a genetic diagnosis was one important step in their overall goal of helping their child live their best life possible life. They intended to use the result as a tool to help their child by seeking the correct school placement and obtaining benefits and therapeutic services. Conclusions: For the parents of children with IDD, the search for a genetic diagnosis is best conceptualized as a part of parents' ongoing efforts to leverage various diagnoses to obtain educational and therapeutic services for their children. Cleaving parents' search for a genetic diagnosis from these broader efforts obscures the value that some parents place on a sequencing result in finding and tailoring therapies and services beyond the clinic. Interviews with parents reveal, therefore, that genomic sequencing is best understood as one important stage of an ongoing therapeutic odyssey that largely takes place outside the clinic. Findings suggest the need to expand translational research efforts to contextualize a genetic diagnosis within parents' broader efforts to obtain educational and therapeutic services outside clinical contexts.